Perception of the educational environment by students of medical faculty of the Dnipro State Medical University - Stanishevska , N.V.; Chobitok , L.A. (Морфологія / Morphologia / Morfologìâ, 2022)
The success of the educational process in many aspects depends on the educational environment created by the learning conditions. For students of the first two years, adaptation to the learning environment will be easier and faster, the better all participants in this process are aware of which factors are determining. In order to provide feedback to students, which allows to assess the reaction to the educational environment in some institutions of higher education in the United Kingdom of Great Britain, Australia, India, China, Germany, Sweden, etc. from time to time, teachers conduct monitoring studies that help to assess, in addition to the educational environment, also psychological state and social perception of students. Purpose To study the perception of the conditions of the educational environment by domestic students of the 1st and 2nd courses of the Dnipro State Medical University. Methods. The DREEM indicator (Dundee Ready Education Environment) was used as a research method. This indicator consists of five subdivisions, each of which reflects one or another aspect of the educational environment as a whole, namely: the educational atmosphere and the social self-perception of students, the perception of teachers by students or teaching; academic self-perception and perception of learning. The assessment of the above-mentioned aspects of the educational environment is carried out by a questionnaire consisting of 50 statements. Each statement is rated by the student on a 5-point scale, where 4 - "I completely agree", 3 - "Agree", 2 - "Not sure", 1 - "Disagree", 0 - "Absolutely disagree". An ideal educational environment corresponds to 200 points. A number of statements correspond to each aspect, and for each aspect of the educational environment, an average score and a standard deviation are calculated. Results. The study was conducted among 200 students of the specialty "Medicine", according to which the overall positive average score was 149,2/200 (74.6%), which reflects rather a positive perception of the educational environment by students of the Dnipro State Medical University. Among the categories, the perception of learning was rated very high – 38,2/48 (80%). Also, students gave rather high marks to the academic self-perception category -25,07/32 (78%). Educational atmosphere and social self-perception received -36,64/48(76%) and 19,52/28(70%), respectively. The perception of teaching when converted into percentages had the lowest score among students 29,74/44 (68%). Conclusion. Using the DREEM indicator, a study was conducted of the perception of the educational environment by 1st and 2nd year students of the Dnipro State Medical University, according to the results of which it can be summarized that the educational environment as a whole is perceived by students as positive, but has certain disadvantages. The obtained estimates of the categories of the educational process make it possible to make an analysis to eliminate the problems and shortcomings of the latter and may be a prerequisite for correcting the conditions of the educational environment and relations between students and teachers, which should help improve the educational process.